PERTUMBUHAN SETEK BERBAGAI KULTIVAR KRISAN (Chrysanthemum morifolium R.) PADA PEMBERIAN JENIS AUKSIN BERBEDA - Rahman, Agus; Setyono, Setyono; Winarto, Budi (Universitas Djuanda Bogor, 2018)
This study aims to obtain qualified seedlings, and speed up the rooting of some varieties of chrysanthemum (Chrysanthemum morifolium R.) cuttings use synthetic and naturally plant growth regulator (auxin).Â Research results are expected to be an alternative method of application effective and environmentally friendly plant growth regulator. The research was conducted from March to April 2013 at the Research Institute of Ornamental Plants (Balai Penelitian Tanaman Hias). The experimental design used is completely randomized design (CRD) factorial. The first factor is the type of auxin which consists of four levels ie control, indole acetic acid (IAA), naphthalene acetic acid (NAA), pregnant cow urine, and not pregnant cow urine. The second factor is the type of chrysanthemum varieties which consists of four levels ie spray type of Puspita Pelangi, spray type of Puspita Nusantara, standard type of Sakuntala, and standard type of Pasopati. The results showed that type of chrysanthemum cultivars and type of auxin not affected the percentage of live cuttings, percentage of rooted cuttings and percentage of sprouted cuttings. The cuttings root of plant that given by pregnant cow urine is better than other treatments. Cuttings root length, and number of primary root of Pasopati is better than other cultivars. The interaction influence between the type of auxin and chrysanthemum cultivars found only in the number of secondary roots, diameter of root and length of the shoot cuttings at 12 DAP.Keywords: Chrysanthemum morifolium R., cow urine, NAA, spray type